Women Correctional Officers in California, 1979 - Holeman, Herbert ([Verlag nicht ermittelbar], 1987)
This study examined women correctional officers working in the 11 institutions for men operated by the California Department of Corrections in 1979. For Part 1, Census, researchers conducted a census of all 386 female correctional officers working in these institutions to collect demographic characteristics and baseline data. For Parts 2 (Staff) and 3 (Inmate), a survey was administered to staff and inmates asking their opinions about differences in performance between male and female correctional officers. Part 4, Profile, contains demographic and background data for the officers participating in the Part 2 survey. For Parts 5 (Female) and 6 (Male), researchers gathered job performance data for female correctional officers in 7 of the 11 institutions, as well as a matched sample of male correctional officers. Variables in Parts 1 and 4-6 include demographic information such as age, ethnicity, marital status, number of children, and educational and occupational history. Other variables measure attributes such as age, weight, and height, and record career information such as date and location of permanent assignment as a correctional officer, any breaks in service, and other criminal justice work experience. Additional variables in Parts 5 and 6 include job performance measures, such as ratings on skills, knowledge, work habits, learning ability, overall work habits, quality and quantity of work, and commendations. Parts 2 and 3 present information on staff and inmate evaluations of male and female correctional officers performing specific roles, such as control work officer, yard officer, or security squad officer. Additional variables include opinions on how well male and female officers handled emergency situations, maintained control under stress, and used firearms when necessary. Questions were also asked about whether inmates' or officers' safety was endangered with female officers, whether women should be hired as correctional officers, and whether female officers were gaining acceptance in correctional facilities.